Selective one-pot chemical recycling of PET waste to xylene monomers: insights into a Ru/TiO2 catalyst design and interfacial dynamics in a biphasic system - Murali, Vishnu; Kim, Hanbyeol; Kim, Han Ung; Kim, Jung Rae; Son, Sang Hwan; Park, Young-Kwon; Ha, Jeong-Myeong; Jae, Jungho (Royal Society of Chemistry, 2025)
This study presents a significant advancement in the conversion of waste polyethylene terephthalate (PET) into benzene, toluene, and xylene (BTX)-valuable aromatic monomers-via a single-step catalytic pathway. Investigating the effect of the TiO2 support's morphology revealed that commercial P25, with its hydrophilic properties, was the optimal support for BTX production. Its capability to form a stable oil/water (O/W) emulsion facilitated the efficient transport of depolymerized PET monomers to the oil phase, enhancing the hydrogenation and deoxygenation of oxygenated aromatic hydrocarbons. Examining the influence of Ru particle size (0.9-2.1 nm) on BTX production showed that smaller Ru particles enhanced activity for forming unsaturated cyclic hydrocarbons. The catalyst (2 wt% Ru/TiO2-P2-400), prepared using the polyol method, achieved nearly complete PET conversion and similar to 99% selectivity for BTX under mild conditions (220 degrees C, 10 bar H2, 12 h). Additionally, the study highlighted the role of strong metal-support interactions (SMSIs) achieved at a reduction temperature of 400 degrees C, which significantly improved PET hydrodeoxygenation (HDO) efficiency by promoting C-O bond cleavage through an undercoordinated pathway. Ru nanoparticles located in the inner interfacial layer of the Pickering emulsion accelerated deoxygenation, which was crucial for BTX formation. These findings underscore the importance of optimizing catalyst design, Ru particle size, and interfacial dynamics to achieve high selectivity and efficiency in PET recycling.